A novel electro-synthesis of hierarchical Ni–Al LDH nanostructures on 3D carbon nanotube networks for hybrid-capacitors. (5th January 2023) - Zhang, Dingyue; Zhao, Mingqing; Zhang, Hao; Terrones, Mauricio; Wang, Yanqing
Abstract: Despite the advantages of fiber-shaped supercapacitors (FSCs) in powering wearable electronics, the low energy density dramatically hinders their practical application. Asymmetric configuration design especially with pseudocapacitive materials is an effective solution due to the extended voltage window and large pseudocapacitance. In this paper, a flexible asymmetric FSC is designed, which uses carbon fiber (CF) as the substrate, multi-layer alternating Ni–Al layered double hydroxide/mono-dispersed carbon nanotube (CNT) coaxial layer ([Ni–Al LDH-x/CNT-y]@CF) as the positive electrode material, and tremella-derived activated carbon@CF (TDC-z) as negative electrode material. The 3D Ni–Al LDH/CNT network can realize high-quality loading, rapid electron transfer, effective ion diffusion, and mechanical stress release. The obtained [Ni–Al LDH-2/CNT-2]@CF composite has a large specific capacitance of 1800 F g −1 and high capacity retention of 65.8% at a current density of 10 A g −1 . Based on that, the resulting Ni–Al LDH-2/CNT-2]@CF//TDC-800@CF achieves a remarkable energy density of 35.6 Wh kg −1, a power density of 7531.90 W kg −1, and superior cycling stability of 124.8% over 5000 cycles at a current density of 10 A g −1 . These encouraging results indicate that our hybrid FSC has clear potential as a wearable/flexible energy storage device. Graphical abstract: Schematic diagram of the preparation of [Ni-Al LDH-x/CNT-y]@CF fiber electrode and its capacitor properties. Image 1